Temporary work in Tuscany: A multinominal nested logit analysis - Lorenzo Corsini; Marco Guerrazzi (The Open University, Economics Department, 2007)
In this paper, distinguishing between the choice of the worker and the choice of the firm, we provide a probabilistic evaluation of the transition from temporary to permanent employment in a regional context. Estimating a Multinomial Nested Logit Model, we found that the transition to a permanent job is far from certain, especially for women and older workers.
Keywords: C25; J24; K31; 330; Temporary Jobs; Multinomial Nested Logit Model; Stabilization Probability; Befristeter Arbeitsvertrag; Arbeitsmarktflexibilität; Qualifikation; Geschlecht; Logit-Modell; Schätzung; Toskana; Italien